Representing and Capturing the Experts´ Knowledge in a Design Process - Gonnet, Silvio Miguel (2003)
An object-oriented framework to support the modeling and management of the design process is introduced. It naturally integrates the representation of both the design process itself, and the outcomes that are achieved as the result of the various design activities. The integral view of tracing that was adopted not only captures and manages the products being generated but also the activities that occurred, their associated context and the adopted decisions. The Version Administration System introduced in this paper provides an explicit mechanism to manage the different model versions being generated during the course of a design project as design activities are executed.